Such a perfect wife : a novel - White, Kate, 1950- (White, Kate, 1950- Bailey Weggins mystery., 2019)
On a sunny morning in late September, Shannon Blaine sets off for a jog along the rural roads near her home in Lake George, New York. It<U+2019>s her usual a.m. routine, her “me time” after dropping the kids off at school<U+2026>except on this day she never returns. Is her husband lying when he says he has no clue where she is? Could Shannon have split on her own, overwhelmed by the pressures of her life? Or is she the victim of a sexual predator who had been prowling the area and snatched her before she knew what was happening. True crime writer Bailey Weggins, on assignment for the website Crime Beat, heads north from New York City to report on the mysterious disappearance. An anonymous tip soon leads Bailey to a grisly, bone-chilling discovery. Every town has its secrets, Bailey reminds herself, and nothing is ever as perfect as it seems. She keeps digging for answers until<U+2014>when it<U+2019>s almost too late<U+2014>she unearths the terrifying truth.